COUNSELING ON THE IMPORTANCE OF EARLY EDUCATION AND ISLAMIC LEARNING IN MEKARSARI VILLAGE: PENYULUHAN PENTINGNYA PENDIDIKAN PADA USIA DINI DAN PEMBELAJARAN AGAMA ISLAM DI DESA MEKARSARI - Dini Martinda Lestari; Muhammad Zhaclin Arkal; Sofwan Afif (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Elementary education or elementary school is the initial momentum for children to improve their abilities, from elementary school they get immunity to learning which then becomes a habit they do in the future. It has been realized that the younger generation is the next generation that needs to be nurtured from an early age, so that early development is the responsibility of the family, environment and society. This period is a golden period for children's development to the educational process. This period is valuable years for a child to recognize various facts in the environment as a stimulus for personality, psychomotor, cognitive and social development. For this reason, early childhood education in the form of stimulation (stimulation) from the closest environment is needed to optimize children's abilities. Do not forget also the importance of religious education. One of the things that must be given at an early age is religious education. With mature religious education from an early age, it can help children's development, especially in terms of attitudes and behavior.